Caixa da ditongação: trabalhando a interferência da oralidade na escrita de alunos do ensino fundamental - Santos, Ederlaine Araujo dos (2021)
In this paper, we developed a study on the phonological process of diphthongization in the writing of 9th grade students from a public school located in Areia Branca - Sergipe, Brazil. In speech, diphthongization occurs spontaneously and usually goes unnoticed; however, in writing, this phenomenon is considered a spelling error, and it is often a source of discrimination and censorship. The confirmation of the presence of the diphthongization in the students’writing leads us to reflect on what would be motivating this occurrence. In this sense, we argue that the phenomenon of diphthongization is promoted by the influence of speech on writing. The product consists of the creation of a play box named “diphthongization box”, which contains four sets that promote the writing of words that favor diphthongization. Thus, we understand the relevance of this study as well as of the educational product for the treatment of the diphthongization phenomenon in a playful way, assisting the teacher to work the orthographic norms under a new teaching approach. Among the authors from whom we sought support to ground this research are: Callou and Leite (2005), Câmara Júnior (2011, 2015), and Silva (2019) with theories on phonology and phonological processes; and Morais (2001), Cagliari (2002), Bortoni-Ricardo (2004, 2005) with studies on spelling, linguistic variation, and teaching. Our work is fundamentally based on the methodological assumption of Action- Research, since it is characterized as a line of investigation associated with forms of collective action, focused on problem-solving or transformational objectives, as stated by Thiollent (2002) about this type of research. The data were collected by applying an activity that included writing the names of figures. Once this material was available, it was possible to identify the phonological processes present in the participants’ writing and choose which had the most occurrences - diphthongization.